Microbial metabolite effects on TLR to develop autoimmune diseases. (2nd October 2019) - Mohseni Moghadam, Zeinab; Mahmoodzadeh Hosseini, Hamideh; Amin, Mohsen; Behzadi, Elham; Imani Fooladi, Abbas Ali
Abstract: The mammalians harbor and are exposed to various populations of microorganisms, that interact with the immune system and are able to affect the balance of immune responses. Modifications of commensal flora can result in dysregulation of immune responses. Toll-like receptors (TLRs) are not only of importance in eliciting the immune responses against pathogens, but also show a significant role in the homeostasis of commensal microbiota and in the response to hazard signals and stress. Here, we review a summary of the TLRs function and the relationship between the immune system and the microbiome in autoimmune diseases' development.